MATH GAMES DOMINO EFFECT ON THE RESULTS OF THE LEARNING MATH FRACTIONS IN CLASS IV SD NEGERI 1 KALIKABONG - Sri Muryaningsih; Sony Irianto (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2015)
The purpose of this study was to determine: 1) the influence of mathematical domino game against cognitive aspects of mathematics learning outcomes, 2) the influence of mathematical domino game against affective aspects of mathematics learning outcomes 3) the influence of mathematical domino game against psychomotor aspects of mathematics learning outcomes. The research method using experimental research methods to design randomized control group pretest-posttest design. The samples in this study using cluster random sampling. The population in this study is the fourth grade students of SD Negeri 1 and 2 Kalikabong second semester of academic year 2014 / 2015. The experimental classes will be treated mathematics with math domino game material fractions, while grade control using conventional learning. Instruments cognitive aspects of learning outcomes research using test descriptions, research instruments affective aspects of learning outcomes using a questionnaire, and research instruments psychomotor aspects of learning outcomes using performance assessment sheet. Analysis of survey data using statistical analysis independent sample t test with SPSS program. The results showed: 1) a game of dominoes mathematical better effect on the results of the cognitive aspects of learning mathematics, 2) math domino game better effect on the results of the affective aspects of learning mathematics 3) math domino game better effect on psychomotor aspects of mathematics learning outcomes.